2004
DOI: 10.1021/jf048743h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Catechol Lignans Converted from Sesamin and Sesaminol Triglucoside by Culturing with Aspergillus

Abstract: Sesamin and sesaminol triglucoside in sesame seeds are major lignans that display an abundance of biological activities. Although their antioxidative activity in vitro is weak, they have been reported to suppress oxidative stress in vivo. We investigated the production of new antioxidative lignans from sesame lignans by culturing with the genus Aspergillus to enhance the function of food materials. Media containing sesamin or sesaminol triglucoside increased antioxidative activity for DPPH radical scavenging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 21 publications
3
62
1
Order By: Relevance
“…Previous studies demonstrated that sesamin is metabolized to sesamin dicatechol via sesamin monocatechol in rats (Nakai et al, 2003;Peñalvo et al, 2005;Liu et al, 2006). It is noted that sesamin dicatechol is a more potent antioxidant than sesamin monocatechol (Nakai et al, 2003;Miyake et al, 2005). Thus, the conversion from monocatechol to dicatechol is pharmacologically important.…”
Section: Metabolism Of Sesamin By Human P450mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that sesamin is metabolized to sesamin dicatechol via sesamin monocatechol in rats (Nakai et al, 2003;Peñalvo et al, 2005;Liu et al, 2006). It is noted that sesamin dicatechol is a more potent antioxidant than sesamin monocatechol (Nakai et al, 2003;Miyake et al, 2005). Thus, the conversion from monocatechol to dicatechol is pharmacologically important.…”
Section: Metabolism Of Sesamin By Human P450mentioning
confidence: 99%
“…Liu et al (2006) proposed tentative metabolic pathways of sesamin. Among the 11 kinds of the metabolites, mono-and dicatechol metabolites, which appear to be metabolized by P450s, are known to have high antioxidative activities (Nakai et al, 2003;Miyake et al, 2005). It was reported that sesamin elevated CYP2B and CYP4A mRNA levels in rats (Tsuruoka et al, 2005;Ikeda et al, 2007) and CYP1A activity in rainbow trout (Trattner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They have the pharmacological properties including anti-inflammatory 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 effects [11], antioxidant activity [12], antihypertensive effects [13], apoptosis-induction in tumor cells [14], enhancing antioxidant activity of vitamin E [15], lowering cholesterol levels [16], improving fatty acid metabolism [17], and neuroprotective effects against hypoxia [18]. Recently, we reported that sesamin treatment in vitro reversed pathological changes in OA cartilage: reduced the disorganization of chondrocytes in cartilage, increased cartilage thickness and decreased losses of type II collagen and CS-PGs [11].…”
mentioning
confidence: 99%
“…The frequency of the CYP2C19*17 allele is high (18%) in Ethiopians and Swedes (Sim et al, 2006), 0.64% in Chinese (Wang et al, 2009), and 1.3% in Japanese (Sugimoto et al, 2008). The antioxidant effects of episesamin in ultra-rapid metabolizers might be larger than those in normal metabolizers because of a high ability of dicatechol formation (Nakai et al, 2003;Miyake et al, 2005). However, CYP2C19 poor metabolizers, whose frequency is approximately 20% in Japanese and Koreans, appear to have a low ability to form episesamin dicatechol.…”
mentioning
confidence: 99%